THE APPLICATION OF SUPERVISION BY VISITATION IN IMPROVING THE ABILITY OF TEACHERS IN THE CLASSROOM LEARNING PROCESS AT UPT SMP NEGERI 11 GRESIK - Sumarno Sumarno (LPPM STAI Muhammadiyah Probolinggo, 2022)
This study aims to improve the ability of teachers during learning process in the classroom through the implementation of supervision, particularly by visitation. The research focus in the classroom is the ability of teachers in conducting the learning process. Teacher's ability in identifying learners' is around 15 teachers or 60 %. Other focuses cover the ability of teachers to motivate students to learn actively and the ability to conduct classroom management, the ability of teachers to identify students' behavior and develop students' potential and overcome the students' shortcomings, as well as the ability of teachers to observe to student weaknesses. This research was conducted in UPT SMP Negeri 25 Gresik for a month. The results showed that the supervision process by visitation is very effective in improving the ability of teachers in learning management